Determinants of Behavior and Exclusive Breastfeeding: Logistic Regression Test On Babies Aged 7-12 Months - Reynalda Pooja Lestari; Awis Hamid Dani; Lilis Banowati; Laili Nurjannah Yulistiyana; Suzana Indragiri; Iin Kristanti; Cucu herawati (Promotif : Jurnal Kesehatan Masyarakat, 2025)
Introduction: Research purposes this for analyze knowledge, patterns of nurturing, and support families to exclusive breastfeeding.? Methods: Types of research quantitative design cross-sectional, a population is a mother who has babies 7-12 months old as many as 90 respondents, and techniques taking a sample with simple random sampling. Data collection method with interview. Data was analyzed using a multivariate logistic regression test. Ethical permission for this research was obtained from the research and community service institute, Cirebon College of Health Sciences with number No.045/LP3M_STIKes Crbn/IV/2023. Results: Research results show exists connection between knowledge (p-value 0.001), pattern foster (p-value 0.001), and support family (p-value 0.003) with exclusive breastfeeding.? Analysis multivariate obtained pattern foster as the most influential variable to exclusive breastfeeding (OR=9.357), meaning mother who has pattern foster not enough have risk more than 9 times big no give exclusive breast milk to the baby. Conclusion: Public health centers are expected to increase efforts promotion of health. Should mothers increase attention and time for babies. For working mothers,? It's best to regularly pump breast milk at home or the office. Mothers increase awareness of will importance look after healthy babies by providing exclusive breastfeeding.